2020
DOI: 10.1038/s41598-020-76327-4
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular functions may be impaired in children diagnosed with subclinical hypothyroidism

Abstract: Subclinical hypothyroidism (SH) may influence both ventricular functions. The aim of this study was to evaluation the findings of Tissue Doppler Imaging (TDI) and other echocardiography modalities in children with SH. We compared left ventricular mass index (LVMI) and TDI parameters of patients with SH and children with euthyroidism. Subclinical hypothyroidism was diagnosed when thyroid stimulating hormone level was higher than the reference value of the laboratory (> 4.2 mIU/L) and free thyroxine level was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We also found that the combination of LVMI and RWT is predictive of the outcomes after LT in children with BA. Elevated LVMI and RWT are used to identify left ventricular hypertrophy (LVH), which has been related to poor outcomes, including death, in both adults and pediatric patients with cirrhosis, and has also been related to morbidity in other diseases (8,(18)(19)(20). At present, there are no established thresholds for determining LVH in children.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the combination of LVMI and RWT is predictive of the outcomes after LT in children with BA. Elevated LVMI and RWT are used to identify left ventricular hypertrophy (LVH), which has been related to poor outcomes, including death, in both adults and pediatric patients with cirrhosis, and has also been related to morbidity in other diseases (8,(18)(19)(20). At present, there are no established thresholds for determining LVH in children.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with that of another systematic evaluation based on echocardiography, cardiac magnetic resonance imaging, and myocardial radionuclide imaging, which found no significant morphological changes in the heart after treatment with levothyroxine in patients with SCH ( 30 ). Some studies have suggested that the LV mass of both adult and pediatric patients with SCH is significantly increased compared to that in the normal population ( 14 , 31 ) and that this increases with the duration of the disease among those with TSH≥10.0 ( 32 ). However, other studies have reported no significant association between SCH and LV mass ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of thyroid hormones are associated with myocardial infarction, decreased cardiac output, altered heart rate, increased systemic vascular resistance, cardiomyocyte atrophy, endothelial dysfunction, and increased prevalence of atherosclerosis and heart failure (8). It has been observed that subclinical hypothyroidism is associated with left ventricular systolic and diastolic dysfunction (9,10). Changes in thyroid hormone levels increase the hemodynamic load of the heart, which increases the heart rate and ultimately the size of the heart (11).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial-dependent vasodilation disorder has been reported as a result of nitric oxide reduction in subclinical hypothyroidism (15). The role of these hormones in heart failure has been identified, but limited studies have examined the systolic and diastolic ventricular disorders in detail (6,9,10,12).…”
Section: Introductionmentioning
confidence: 99%